EVALUASI KEBIJAKAN PENGELOLAAN SAMPAH DI TEMPAT PEMROSESAN AKHIR BANTAR GEBANG DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN SAMPAH - Riefqy Hasbi Al Baihaqi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The purpose of this study is to evaluate the effectiveness of waste management policy implementation at the Bantar Gebang Landfill as the largest landfill in Indonesia, to identify the main challenges in its implementation, and to analyze the technical, institutional, and social factors that influence the success of urban waste management policies. The study uses a qualitative approach with a descriptive evaluative research design. Data are collected through in-depth interviews with relevant informants, direct field observations, and documentation studies of regulations and waste management reports. The data analysis process follows systematic stages, including data reduction, data display, and conclusion drawing, in order to obtain a comprehensive understanding of the ongoing policy implementation. The findings show that the implementation of waste management policy at the Bantar Gebang Landfill is not yet optimal. The main obstacles include limited landfill capacity, insufficient human resources, limited funding and technology, and weak institutional coordination. In addition, the significant environmental and social impacts indicate a gap between policy objectives and field realities. These findings contribute to the development of environmental policy implementation studies and provide a basis for formulating strategic recommendations to improve the effectiveness of integrated and sustainable waste management.